PENGARUH SUKU BUNGA, PELAYANAN DAN KESADARAN MEREK (BRAND AWARENESS) TERHADAP KEPUTUSAN PENGAMBILAN KPR (STUDI PADA NASABAH PT BANK TABUNGAN NEGARA KANTOR CABANG SEMARANG) - Laely Hidayah; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2016)
This research was motivated by fact that there’s a high demand of fund distribution for the purchase of a home. Bank Tabungan Negara Semarang one of the state banks that focus on lending in housing finance. To be able to compete with other banks, PT. Bank Bank Tabungan Negara Semarang will have to pay attention to the interest rate charged, the service provided and emphasize brand awareness of the mortgage product in order to attract customers. Type of this research is explanatory research. This study aims to determine the influence of interest rates, service and brand awareness has an influence on the decision making of mortgage. The sample in the research is 100 respondents who are mortgage customers. The results showed that Interest rates had the most impact of 10,7%, service have influence of 5,5% and brand awareness influence of 5,7%. Simultaneously interest rates, service and brand awareness have contributed 22,6% of the mortgage decision-making. Suggestions for companies are should lower the mortgage rates in order to compete, improve the quality of service and increase brand awareness mortgage of BTN product in the minds of consumers.